Etnofarmakologi Tumbuhan Mangrove Achantus ilicifolius L.,Acrostichum speciosum L. dan Xylocarpus rumphiiMabb.Di Desa Sungai Tekong Kecamatan Sungai Kakap Kabupaten Kubu Raya - Riza Linda, Sri Wedari Ernianingsih, Mukarlina (Jurnal Protobiont, 2014)
Mangrove forest is a very useful area to protect coast from abrasion and also serves benefits for coastal community such as materials for medicines. The aim of this study was to determine the contents of phytochemical compounds in mangroves Achantus ilicifolius, Acrostichum speciosum and Xylocarpus rumphii those have been used as materials for medicines by the villages of Sungai Tekong village, Sungai Kakap district of Kubu Raya regency. The study was conducted in March to June 2014 at Sungai Tekong village and Biology Laboratorium of Math and Sciences Faculty of Tanjungpura University. The method used were semi-structurized interviews and phytochemical test. The result showed that mangroves Achantus ilicifolius, Acrostichum speciosum and Xylocarpus rumphiithose have been used as a medicine contain phytochemical compounds such as alkaloid, saponin, terpenoid, flavonoid and phenol. The diseases those might be cured with those mangroves and rheumatism, ulcers, hypertention, intestinal worms, hepatitis, asma, flatulence, restore power after childbirth, diarrhea, mouth sores, mumps, malaria, dysentry, ulcers, cholera, sampu, and to protect the skin from the sunlight.